Konstruksi Maskulinitas Boyband 2PM pada Remaja Penggemar K-Pop - Alna Hanana; Annisa Rahma (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2018)
This research is done toward a die-hard fan of a Korean phenomenon boyband named 2PM. The purpose of this research is to discover how masculinity being constructed by a teenage girl fan of 2PM by considering her background, lifestyle and media consumption. The data were collected by means of deep interview and observation. The output showed that the codes which related to masculinity were not always decoded exactly the same way. How a decoder decodes changed as a decoder exposed by the codes through media more intensely time after time. The implication of this research showed that there is several lack of fit between codes that encoded by the encoder and decoded by the decoder so that the identities within the codes were not identified.